Activity Of Sodium Bicarbonate Against Escherichia Coli - AL-Khikani, Falah Hasan Obayes; Nima, Aymen Raad; Salah, Aymen Mahdi; Noor, Bassim Ibrahim Hadi , Baneen Hameed Badran , Baneen Karim Ghazi, Tamim Fouad Darwes, Hassan Majed Abd Alabaas, Tabark Ajme Tourki , Tabark Hameed (Medical Science Journal for Advance Research, 2023)
Background: Escherichia coli (E. coli) are one of the most common bacteria that can be pathogenic and develop resistance to various antibiotics by different ways, making them difficult to treat with standard therapies. So, using alternative strategies in management are urgent. Material and methods: The bacteria (E. coli) was isolated from urinary tract and wounds; cultured in three media (blood agar, macConkey agar, and eosin methylene blue agar). Sodium bicarbonate (SBC) with three concentrations (20%, 10%, and 5%) evaluated as antimicrobial agents against isolated E. coli by well diffusion method. The antibiotics discs (Gentamicin) were used by disc diffusion method as control agents. All the statistical analysis was done by using SPSS 26 software and Excel app. Results: Out of the 24 specimens in the study, 66.6% were women, while 33.4% were men with significant differences (P< 0.05). E. coli revealed 70.8 % sensitivity to gentamicin. 66.6 %, 62.5 %, and 58.33 % of E. coli were sensitive to 20%, 10%, and 5% SBC respectively. The mean comparison of inhibition zone of 20 % SBC 13.42± 11.75 mm with gentamicin 15± 6.43 mm showed no significant statistical differences (P= 56) that’s mean 20% SBC is equal in antibacterial activity to gentamicin. Other concentrations of SBC (10% and 5 %) also showed no significant differences compared to gentamicin (P= 21 and P= 0.16) respectively. Conclusions: The antibacterial activity of SBC makes it a promising candidate for the development of new antimicrobial agents.